Identification and functional analysis of Dmrt1 gene and the SoxE gene in the sexual development of sea cucumber, Apostichopus japonicus - Liu, Bing-Zheng; Cong, Jing-Jing; Su, Wei-Yi; Hao, Zhen-Lin; Sun, Zhi-Hui; Chang, Ya-Qing (Frontiers in Genetics, 2023)
Members of the Doublesex and Mab-3-related transcription factor (Dmrt) gene family handle various vital functions in several biological processes, including sex determination/differentiation and gonad development. In particular, Dmrt1 and Sox9 (SoxE in invertebrates) exhibit a very conserved interaction function during testis formation in vertebrates. However, the dynamic expression pattern and functional roles of the Dmrt gene family and SoxE have not yet been identified in any echinoderm species. Herein, five members of the Dmrt gene family (Dmrt1, 2, 3a, 3b and 5) and the ancestor SoxE gene were identified from the genome of Apostichopus japonicus. Expression studies of Dmrt family genes and SoxE in different tissues of adult males and females revealed different expression patterns of each gene. Transcription of Dmrt2, Dmrt3a and Dmrt3b was mainly detected in the tube foot and coelomocytes instead of in gonadal tissues. Dmrt1 was mainly detected in the germ cells of the testes and was mainly expressed in spermatocytes. Knocking-down of Dmrt1 led to the downregulation of SoxE and upregulation of the ovarian regulator foxl2 in the testes. This indicates that Dmrt1 may be a positive regulator of SoxE and may play a role in the development of the testes in the sea cucumber. In contrast, the expression level of SoxE was higher in the ovaries than in the testes and SoxE knockdown in male A. japonicus led to downregulation of Dmrt1 and upregulation of foxl2 in the testes. Meanwhile, SoxE knockdown in female A. japonicus resulted in the downregulation of Dmrt1, foxl2 and the germ cell marker piwi, suggesting that it plays a role in ovary and testis development in the sea cucumber. In summary, this study indicates that Dmrt1 and SoxE are indispensable for testicular differentiation, and SoxE might play a functional role during ovary differentiation in the sea cucumber.